The Utilization Of Palm Oil Mill Effluent For Renewable Energy - Rahma Nuryanti; Tuty Emilia Agustina; Tuti Indah Sari (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
The demand of energy in the world today has increased exponentially, therefore, more efforts have been focused on looking for alternative renewable sources, such as biodiesel, which involves fuel produced from oil of plant, or animal fat. The objective of the research, therefore, was to utilize the palm oil mill effluent (POME) as a raw material in the production of biodiesel, by applying varying solvent, extraction time and the effluent to solvent ratio. Furthermore, the best output of oil rendement of (81.07%), in comparison with the total sample taken,was obtained using n-hexane, at an extraction time of 3 days, and ratio of 1:1. Furthermore, the output possessed a high acid number. Hence, it is considered in the process of esterification and transesterification, required in the production of biodiesel. The HCl catalyst ratio of 1.25% (%v) was used in the esterification process, and the lowest acid number of 2.08 mg-KOH/gr was obtained, followed by the transesterification process, using 1.5% (%w) of NaOH catalyst of the oil weight. Hence, the characteristics of biodiesel produced were in accordance with SNI 04-7182-2006.Keywords: POME, Biodiesel, Esterification and Transesterification, Extraction, n-Hexane